Age-related differences in SARS-CoV-2 binding factors: An explanation for reduced susceptibility to severe COVID-19 among children?. (December 2022) - Abrehart, Thomas; Suryadinata, Randy; McCafferty, Conor; Jacobson, Jonathan; Ignjatovic, Vera; Robinson, Phil; Crawford, Nigel W.; Monagle, Paul; Subbarao, Kanta; Satzke, Catherine; Wurzel, Danielle
Abstract: Context: In contrast with other respiratory viruses, children infected with SARS-CoV-2 are largely spared from severe COVID-19. Objectives: To critically assess age-related differences in three host proteins involved in SARS-CoV-2 cellular entry: angiotensin-converting enzyme 2 (ACE2), transmembrane serine protease 2 (TMPRSS2) and furin. Methods: We systematically searched Medline, Embase, and PubMed databases for relevant publications. Studies were eligible if they evaluated ACE2, TMPRSS2 or furin expression, methylation, or protein level in children. Results: Sixteen papers were included. Age-dependent differences in membrane-bound and soluble ACE2 were shown in several studies, with ACE2 expression increasing with age. TMPRSS2 and furin are key proteases involved in SARS-CoV-2 spike protein cleavage. TMPRSS2 expression is increased by circulating androgens and is thus low in pre-pubertal children. Furin has not currently been well researched. Limitations: High levels of study heterogeneity. Conclusions: Low expression of key host proteins may partially explain the reduced incidence of severe COVID-19 among children, although further research is needed.